Results 1 to 4 of 4

- October 16th 2006, 07:38 PM #1

- Joined
- Oct 2006
- Posts
- 2

- October 16th 2006, 07:42 PM #2

- Joined
- Oct 2005
- From
- Earth
- Posts
- 1,599

- October 16th 2006, 07:51 PM #3

- Joined
- Oct 2006
- Posts
- 2

- October 17th 2006, 05:26 AM #4
Note the format the Jameson used:

6/14 = 7/(x - 3)

First reduce the fraction on the LHS:

3/7 = 7/(x - 3)

Multiply both sides of the equation by 7(x - 3):

7(x - 3)*(3/7) = 7(x - 3)*[7/(x - 3)]

3(x - 3) = 7*7

3x - 9 = 49

3x = 58

x = 16

Since x is not equal to 3 (this is prohibited by the original expression) this solution is valid.

-Dan